Carlo Martini’s New World Order in Indonesian Context - Mathando Hinganaday, Rafael (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
Diversity has been an unavoidable reality. People live with other people of different religions, tribes, or races. The falling of old ideological and political structures in the world has played a great role in making this happen. To replace the old ideological and political structures, populism tends to be widely accepted by people who want to erect great wall in order to avoid immigrants. In Indonesia, populism manifests in the ideas and attitudes that alienate others based on religions and ethnic groups. The author introduces the views of Carlo Maria Martini, who, as a Catholic bishop, has promoted the idea of creating a society that supports diversity to be a new world order. Martini based his ideas on a biblical analysis, mainly on the Old Testament books such as Genesis, Exodus, and Deuteronomy. In order to find inspiration of Martini’s views for the context of Indonesia, the author relates them to Anthony Giddens and Raimon Panikkar, and finds how Martini’s ideas can be practised not only by inclusivists and pluralists, but also by exclusivists.